2018
DOI: 10.1108/ils-10-2017-0107
|View full text |Cite
|
Sign up to set email alerts
|

Workplace information literacy skills

Abstract: Purpose -The purpose of this study is to investigate the level of information literacy (IL) skills competency among university library professionals in Karachi, Pakistan, and to address areas of concern.Design/methodology/approach -An online survey was designed, using Google Forms, to collect data from 77 academic librarians working in 25 universities in Karachi, Pakistan. Questions covered 6 generic attributes: library systems, information resources, searching techniques, research support, information literac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
0
7
1
Order By: Relevance
“…This finding is also partially in line with the results of Zhang and Wang (2022) who reported that the investigative journalists recruited from different countries had average levels of information skills and literacy in the era of social media. However, this finding contradicted that of many other relevant studies in Pakistan addressing IL in other professional contexts such as scientists (Anwar, 1981;Naveed, 2022;Naveed and Rafique, 2018), investigation officers (Naveed and Kamran, 2022), lawyers (Naveed and Shah, 2022), teachers (Rafique, 2014;Santos and Oliveira, 2013) and librarians (Ali and Richardson, 2018) as these studies reported that the IL skills of the survey participant were not at the optimum levels.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…This finding is also partially in line with the results of Zhang and Wang (2022) who reported that the investigative journalists recruited from different countries had average levels of information skills and literacy in the era of social media. However, this finding contradicted that of many other relevant studies in Pakistan addressing IL in other professional contexts such as scientists (Anwar, 1981;Naveed, 2022;Naveed and Rafique, 2018), investigation officers (Naveed and Kamran, 2022), lawyers (Naveed and Shah, 2022), teachers (Rafique, 2014;Santos and Oliveira, 2013) and librarians (Ali and Richardson, 2018) as these studies reported that the IL skills of the survey participant were not at the optimum levels.…”
Section: Discussioncontrasting
confidence: 66%
“…Santos and Oliveira (2013) provided an insight into the use of IL skills among librarians in Brazil. Ali and Richardson (2018) investigated the levels of IL skills among university librarians in Karachi and reported that these library professionals had good skills particularly for searching for information resources and had low levels of overall IL skills.…”
Section: Workplace Information Literacy (Wil)mentioning
confidence: 99%
“…Though workplace information literacy is getting tremendous popularity among international researchers, there is a dearth of research in the local context. In Pakistan, only a few researchers have targeted different professionals in the context of WIL (Ali and Richardson, 2018; Anwar, 1981; Naveed, 2022; Naveed and Rafique, 2018). These studies investigated scientists, teachers, and library professionals.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, he indicated the future role of librarians and skills in detail such as digital and data librarian, embedded librarians, educator of multiliteracy, licence negotiator, knowledge manager and many more. Ali and Richardson (2018) reported that workplace information literacy skills of Pakistani library professionals. Their study reports show that library professionals are good at the basic operational level of library skills such as searching techniques, providing information to the users, marketing and administrative skills, and at the same time, they are bad at library module services, lack of knowledge of copyrights and less knowledge on research supporting software like plagiarism software, reference management software and many other too.…”
Section: Gkmc 734/5mentioning
confidence: 99%